The Study on synthesis and transformations of some of substituted 4-methylquinolin-2(1H)-ones - Duan, Le The; Thanh, Nguyen Dinh; Thanh, Nguyen Thi; Vu, Hoang Thai; Nguyet, Nguyen Thi Minh; Hoai, Le Thi; Ha, Nguyen Thi Thu; Van, Tran Thi Thanh (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 4, 2017)
Some different substituted 4-methylquinolin-2(1H)-ones have been synthesized by closing corresponding (un)substituted acetoacetanildes in the presence of ionic liquid [Bmim]OH. Obtained quinolines were conveted to its 2-chloro derivatives by reaction with POCl 3 . Some compounds of substituted tetrazolo[1,5-a]quinolines were synthesized by acting these 2-chloro derivatives with sodium azide in DMF as solvent. The structures of obtained compounds have been confirmed by using spectroscopic methods (IR, NMR and MS)